Economies' inclusive and green industrial performance: An evidence based proposed index. (10th January 2021) - Halkos, George; Moll de Alba, Jaime; Todorov, Valentin
Abstract: This paper develops and introduces a new evidence-based tool to systematically measure and benchmark the industrial performance of economies with emphasis on their inclusive and green dimensions. By means of international data sources, we build up a composite index, the inclusive and green industrial performance (IGIP) index, which captures different dimensions of the industrial socio-economic inclusiveness and green performance of the world's economies. We carry out an analysis of 83 economies in 2016 to conclude that industrialized economies (Switzerland, Denmark, Germany, the Czech Republic and Austria) outperform significantly other economies even if we notice remarkable differences in performance among economies. Our analysis opens up new avenues for future research supporting new approaches for the structural transformation of economies in line with the aspirations put forward by the international 2030 agenda for Sustainable Development and the Sustainable Development Goals (SDGs).